Analysis of the relationships between the hospitality workforce and job- satisfaction factors according to age, gender, native language, and racial- ethnicity / Chang Lee and Jungwon Lee - Lee, Chang; Lee, Jungwon (Universiti Teknologi MARA (UiTM), Malaysia, 2012)
The purpose of this study is to investigate the relationships between the hospitality workforce and certain job satisfaction factors. It also addresses what aspects of a position an employee believes to be valued and important. A total of 17 attributes were collected and used from each member of 24 properties. Factor analyses were used to determine the subsets of employee job satisfaction and satisfaction with workforce diversity. MANOVA was performed to determine the differences between job-satisfaction factors, overall job satisfaction, and retention according to workers' age, gender, native language, and racial-ethnicity. A relationship between satisfaction with workforce diversity and overall satisfaction was investigated using simple regression analysis. The findings revealed that women are more attached to their work than men are. Tenured workers consider their employment important in terms of belonging to the society and the community. Workforce diversity plays a more important role among those in management positions than it does for subordinate employees. Employees who are a part of the major racial-ethnic group in the workplace tend to have a more sensitive attitude toward workforce diversity.